2002
DOI: 10.1523/jneurosci.22-20-08860.2002
|View full text |Cite
|
Sign up to set email alerts
|

Direct Effects of Calmodulin on NMDA Receptor Single-Channel Gating in Rat Hippocampal Granule Cells

Abstract: NMDA receptors are glutamate-sensitive ion channel receptors that mediate excitatory synaptic transmission and are widely implicated in synaptic plasticity and integration of synaptic activity in the CNS. This is in part attributable to the high calcium permeability of the ion channel, which allows receptor activation to influence the intracellular calcium concentration and also the slow time course of NMDA receptor-mediated synaptic currents. NMDA receptor activity is also regulated by the intracellular calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 54 publications
6
27
0
Order By: Relevance
“…In contrast, the processes underlying the Ca 2ϩ -dependent inactivation of NMDA receptors are less understood. A number of Ca 2ϩ -dependent proteins, including calmodulin, calcineurin, PKC, and ␣-actinin-2, are implicated in the regulation of NMDAR function (Rycroft and Gibb, 2002). Of particular interest in light of our data are the recent reports that striatal-enriched protein tyrosine phosphatase (STEP), which is also expressed in hippocampus, is activated by calcineurin as a result of Ca 2ϩ entry through NMDARs (Paul et al, 2003).…”
Section: Discussionmentioning
confidence: 82%
“…In contrast, the processes underlying the Ca 2ϩ -dependent inactivation of NMDA receptors are less understood. A number of Ca 2ϩ -dependent proteins, including calmodulin, calcineurin, PKC, and ␣-actinin-2, are implicated in the regulation of NMDAR function (Rycroft and Gibb, 2002). Of particular interest in light of our data are the recent reports that striatal-enriched protein tyrosine phosphatase (STEP), which is also expressed in hippocampus, is activated by calcineurin as a result of Ca 2ϩ entry through NMDARs (Paul et al, 2003).…”
Section: Discussionmentioning
confidence: 82%
“…Previous reports demonstrated that N1 CTDs mediate Ca 2ϩ -dependent modulation of NR kinetics. ␣-Actinin and/or calmodulin modulate single-channel gating of NRs via binding sites located within the N1 CTD (30,57,58). These proteinprotein interactions, as well as the phosphorylation status of N1 CTD residues, influence Ca 2ϩ -dependent inactivation of NR macroscopic currents (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…For SK channels, CaM mediates Ca 2ϩ gating, increasing activity, whereas CK2 phosphorylation of SK2-associated CaM reduces channel activity. For NMDA receptors, CaM mediates Ca 2ϩ -induced inactivation (Ehlers et al, 1996;Krupp et al, 1999;Rycroft and Gibb, 2002), whereas CK2 phosphorylation enhances activity (Lieberman and Mody, 1999). Therefore, the activation of CK2 may additively increase the NMDA component of EPSPs, by directly increasing NMDA receptor activity and decreasing the SK-mediated repolarization that favors reblock of NMDA receptors by external Mg 2ϩ ions.…”
Section: Discussionmentioning
confidence: 99%